Finding and promoting a local conservation consensus in a globally important tropical forest landscape - Padmanaba, M.; Sheil, Douglas (2007)
Can democratic processes favour conservation outcomes in the tropics? This study focuses on local viewpoints within a forested landscape of high conservation significance in East Kalimantan (Indonesian Borneo). Stakeholders received posters displaying results from a previous study; these posters emphasised local priorities and views regarding local biodiversity. We assess local attitudes to this information, and consider some implications. Knowledge of, and agreement with, poster content increased among villagers, towns people and civil servants after they received posters. All respondents appreciated the posters and all supported some form of forest conservation. All respondents agreed that biodiversity conservation and local views are vital in land-use planning. All agreed that logging companies need to be better controlled, while 80% consider them a ‘‘major environmental threat’’. These results bolster our belief that involving communities is not only an ethically defensible way to achieve conservation outcomes, but also a pragmatic opportunity to do so.